Effects of berberine and red yeast on proinflammatory cytokines IL-6 and TNF-α in peripheral blood mononuclear cells (PBMCs) of human subjects - Spatuzza, Carmen; Postiglione, Loredana; Covelli, Bianca; Ricciardone, Margherita; Benvenuti, Claudio; Mondola, Paolo; Belfiore, Anna (Frontiers in Pharmacology, 2014)
Background and Aims: Obesity is a condition associated with chronic or acute inflammatory response characterized by an increase of proinflammatory cytokine levels. Peripheral blood mononuclear cells (PBMCs) migrate in adipose tissue inducing synthesis and secretion of adipocytokines as IL-6 and TNF-α. The aim of this study was to investigate the effect of berberine (a natural alkaloid) and red yeast (a natural antioxidant) on IL-6 and TNF-α cytokines release and gene expression, in circulating lipopolisaccarides (LPS) stimulated PBMCs. Methods and Results: PBMCs isolated from whole blood of healthy donors were stimulated with LPS to induce cytokines production; simultaneously cells were treated with increasing doses of berberine and red yeast. The substances were administered alone or in association. IL-6 and TNF-α protein levels in the culture medium and their mRNA levels were assessed by ELISA and real time PCR, respectively. Berberine and red yeast treatment prevented the LPS induction of IL-6 release in the culture medium of PBMCs. In addition, berberine plus red yeast treatment showed a synergic inhibitory effect on IL-6 release at low concentration. Berberine and red yeast showed an inhibitory effect also on LPS induction of TNF-α release exerting a synergic effect mainly at high concentrations. On the contrary, berberine and red yeast did not significantly affect IL-6 and TNF-α mRNA levels induced by LPS. In this case, only concomitant treatment of PBMCs with high doses of berberine and red yeast inhibits LPS induced IL-6 or TNF-α mRNA levels. Conclusions: The results of our study show that both berberine and red yeast were able to carry out anti-inflammatory action through an inhibition of proinflammatory IL-6 and TNF-α protein release. Moreover, when given in combination these substances were able to inhibit IL-6 and TNF-α gene expression in PBMCs activated by LPS. Therefore, these substances could represent a useful pharmacological treatment to reduce the proinflammatory status accompanied with obesity.